(untitled) (Tanzania Journal for Population studies and Development, 2009)
This paper considers the demographic and macroeconomic consequences of HIV/AIDS in Eritrea. Since there has never been census in the country, this study compared two estimates—one by USBC and another by this author. The latter estimate took into consideration some particular episodes that may have impacted the size, age and gender distribution of the Eritrean population. The USBC population estimate and related demographic indicators do not appear to represent the true picture. The paper summarized a hypothesized relation between HIV/AIDS and demographic variables. This is followed by projecting mortality, fertility, population growth, along with expectation of life at birth in the absence and presence of HIV/AIDS. It appears the impact of the disease on the stated demographic variables are relatively minimal—the rates of change being less than 5%. On the other hand, the effect of HIV/AIDS on key macroeconomic variables—including aggregate saving, labour force and dependency ratio—appear to be considerable (more than 5%). In particular, aggregate saving may be reduced by as much as 36.4%.